'Pedigrees in the Ownership of Law Books': Lawyers' Networks, Celebrity, and the Importance of Provenance in Nineteenth-Century Law Texts1. Issue 1 (8th April 2022) - Hoeflich, Michael
Abstract: This article looks at the multiple uses that may be made of provenance marks in law books. The article examines the importance of prior ownership in nineteenth-century law books based on a survey of representative extant private and institutional library and booksellers' catalogues from the period. It uses this data to understand the importance that contemporary lawyers put on volumes with provenance marks and how the trade in these volumes helps historians to understand the legal 'republic of letters' in the nineteenth-century American Bar.